On the role of acylation of transmembrane proteins - Morozová, Diana; Weiß, Matthias (Biophysical journal, 2010)
Acylation is a frequent means to ensure membrane association of a variety of soluble proteins in living cells. However, many transmembrane proteins are palmitoylated, indicating that this posttranslational modification may also serve as a means to regulate protein trafficking. Based on coarse-grained membrane simulations, we find that protein acylation significantly alters the tilting of transmembrane proteins with respect to the bilayer normal. In addition, the proteins' partitioning behavior and cluster formation ability due to hydrophobic mismatching is strongly altered. Based on our results, we propose that acylation is a potent means to regulate the trafficking of transmembrane proteins along the early secretory pathway.